Estimation Local Fractional Lp Normed Spaces for 1≤p<∞ - Abed Habeeb , Nadiha (Pure Sciences International Journal of Kerbala, 2025)
This paper introduces an improvement and generalization of Hadamard inequality by using the spaces of local fractional -normed spaces for , after Jacques Hadamard has presented his inequality in 1893 about bound on the determination of matrices by using the length of its column vectors. In addition, it is sometimes called Hemit Hadamard inequality with its convex function .The inequality that had been generalized to higher dimensions of function is bounded and convex domain in Euclidean space of n dimension .